2016
DOI: 10.1021/acsami.6b10357
|View full text |Cite
|
Sign up to set email alerts
|

Iron Complex Facilitated Copper Redox Cycling for Nitric Oxide Generation as Nontoxic Nitrifying Biofilm Inhibitor

Abstract: In this study, we developed poly(vinyl chloride) (PVC)-solvent casted mixed metal copper and iron complexes capable of catalytic generation of the antibiofilm nitric oxide (NO) from endogenous nitrite. In the absence of additional reducing agent, we demonstrated that the presence of iron complex facilitates a redox cycling, converting the copper(II) complex to active copper(I) species, which catalyzes the generation of NO from nitrite. Assessed by protein assay and surface coverage analyses, the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…While the enhanced biological effects of NO releasing materials have been studied with metal ions like iron and copper, [25][26][27] and polyurethane/metal-organic framework composite materials, 28 the catalytic effects of a much more mammalian cell friendly metal ion, ZnO-NPs, has not been studied until now. In the past, the ability of Zn 2+ to generate to generate NO from SNAP has been studied using a Zn wire and a solution for in vivo biodegradable bare stent and has been found to elevate NO release.…”
Section: Introductionmentioning
confidence: 99%
“…While the enhanced biological effects of NO releasing materials have been studied with metal ions like iron and copper, [25][26][27] and polyurethane/metal-organic framework composite materials, 28 the catalytic effects of a much more mammalian cell friendly metal ion, ZnO-NPs, has not been studied until now. In the past, the ability of Zn 2+ to generate to generate NO from SNAP has been studied using a Zn wire and a solution for in vivo biodegradable bare stent and has been found to elevate NO release.…”
Section: Introductionmentioning
confidence: 99%
“…Contributions from Amal's group concentrated on catalyzing endogenous nitrite to produce NO using copper complexes loaded into poly(vinyl chloride) (PVC) films. [73][74][75] An exemplary study from her group showed the immobilization of both iron and copper complexes into PVC matrices (Figure 3a). [74] Iron complexes were introduced as a reducing agent to convert Cu 2+ to Cu + .…”
Section: Coppermentioning
confidence: 99%
“…[73][74][75] An exemplary study from her group showed the immobilization of both iron and copper complexes into PVC matrices (Figure 3a). [74] Iron complexes were introduced as a reducing agent to convert Cu 2+ to Cu + . Cu-Fe/PVC films generated a surge of up to 125 nM NO from 1 mM nitrite, which is 5 times higher than pure PVC films and Fe/PVC films and 2.5 times higher than Cu/PVC films.…”
Section: Coppermentioning
confidence: 99%
“…This complex immobilized together with [Fe(dttct)] onto the same matrix composed of a system able to generate nitric oxide (NO) from endogenous nitrite through Cu(II) conversion to active Cu(I). Besides nitrifying bacteria biofilm dispersion, the antibiofilm activity of these material was evidenced against Bacillus species [73].…”
Section: Polymeric Systemsmentioning
confidence: 99%